How to Prepare Biological Samples and Live Tissues for Scanning Electron Microscopy (SEM): - Tahemanesh, Kobra; Mehdizadeh Kashi, Abolfazl; Chaichian, Shahla; Joghataei, Mohammad Taghi; Moradi, Fateme; Tavangar, Seyed Mohammad; Mousavi Najafabadi, Ashraf Sadat; Lotfibakhshaiesh, Nasrin; Pour Beyranvand, Shahram; Fazel Anvari-Yazdi, Abbas; et al. (Galen Medical Journal, 2014)
In this article we review the application and procedures involved in scanning electron microscope (SEM) to observe biological and live tissues through using SEM at high resolution. We discuss practical methods for optimizing tissue preservation to achieve the two principal goals of biological specimen preparation: (a) preserving biological structures as close to their living configuration as possible, and (b) rendering them visible with the desired imaging method. We also review and discuss the relative merits of different fixing (chemical fixation and cryofixation), drying (air-drying, critical point-drying, freeze-drying and chemical-drying) and coating procedures of biological specimens with metals to facilitate visualization in the SEM.